2009
DOI: 10.1007/s10529-009-9986-4
|View full text |Cite
|
Sign up to set email alerts
|

A solid-phase adsorption method for PEGylation of human serum albumin and staphylokinase: preparation, purification and biochemical characterization

Abstract: A solid-phase adsorption method was developed to circumvent the disadvantage of the conventional liquid-phase PEGylation, i.e. the heterogeneity of the PEGylated products. The model proteins, human serum albumin (HSA) and staphylokinase (SAK), were adsorbed on the ion exchange chromatography media, followed by PEGylation with succinimidyl carbonate (SC)-mPEG5K and salt elution. Since PEGylation with SC-PEG5K alters the positive charge of the proteins, Q-Sepharose Big Beads and DEAE Sepharose Fast Flow were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…For example, the yield of the modified product is relatively low in the method based on IEC media (25). The mono-PEGylated protein was not well-separated from the multi-PEGylated protein in the SERC method (31).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the yield of the modified product is relatively low in the method based on IEC media (25). The mono-PEGylated protein was not well-separated from the multi-PEGylated protein in the SERC method (31).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Protein-NH 2 Suo's research group has established a solid-phase modification method for PEGylation of human serum albumin (HSA, 66 kDa) and staphylokinase (SAK, 15 kDa) (25). Q Sepharose Big Bead is a cross-linked agarose coated with quaternary ammonium ligand.…”
Section: Pegylation Of Proteins Using Ion-exchange Chromatographymentioning
confidence: 99%
“…It is one of the most commonly used techniques for the purification of PEGylated biomolecules (9,(13)(14)(15)(16)(17)(18)(19)24), especially in large-scale production. In addition, high performance IEC is also successfully applied to the subfractionation of PEG-proteins on the basis of their degree of PEGylation and positional isomerism (24)(25)(26).…”
Section: Ion-exchange Chromatographymentioning
confidence: 99%
“…PAGE, which has been used mainly for the analysis of the PEGylated products during and after reaction, is probably the most widely used non‐chromatographic technique at this time. Although advances have been made regarding the characterization of PEGylated derivates using this technique,14, 15, 44, 45 it is necessary to explore alternative staining techniques to distinguish free PEG and PEGylated proteins in one step. On the other hand, no reports have been found that indicate the use of electrophoresis in two dimensions for the analysis and characterization of PEGylated products, so it may be interesting to carry out research in this area in order to determine the potential of this technique for the present application.…”
Section: Future Trends and Conclusionmentioning
confidence: 99%
“…Regarding this liquid–liquid fractionation strategy it has been reported that one single grafted chain is enough to promote a selective fractionation towards a specific system phase 11. Also, the use of polyacrylamide gel electrophoresis (PAGE) and capillary electrophoresis (CE) has been reported for the analysis of PEGylated proteins 12–15. PAGE has been widely used for the characterization of the PEGylation reaction.…”
Section: Introductionmentioning
confidence: 99%